Physicochemical properties of dietary fiber of bergamot and its effect on diabetic mice - Liu, Huifan; Liang, Jiaxi; Liang, Churong; Liang, Guiqiang; Lai, Jiacong; Zhang, Renying; Wang, Qin; Xiao, Gengsheng (Frontiers in Nutrition, 2022)
Bergamot (Citrus medica L. var. sarcodactylis) contains different bioactive compounds, and their effects remain unclear. Therefore, the structural and bio-function of bergamot dietary fiber were investigated. A sequential extraction procedure was utilized to obtain soluble dietary fiber (SDF) and insoluble dietary fiber (IDF) from bergamot. The main monosaccharide in SDF and IDF is arabinose. SDF had a porous structure, which enhanced the water and oil holding capacity, as well as the cholesterol and glucose adsorption capacity, which was superior to that of IDF. In db/db diabetic mice, SDF and IDF regulated glucose tolerance and controlled blood glucose levels. Reduction of serum total cholesterol, triglycerides, and low-density lipoprotein cholesterol in SDF and IDF could be observed. In summary, SDF and IDF from bergamot effectively promoted health in patients with diabetes.